BEC STUDENTS’ PERCEPTION TOWARDS THE USE OF WEBTOON TO IMPROVE READING COMPREHENSION SKILL - A. Nur Arifa Zati Rajwa; Andi Anto Patak; Andi Hajar (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2025)
This study aims to determine the perception of BEC students on the use of webtoons to improve reading comprehension. This study uses qualitative methods. Data collection techniques using questionnaires and interviews. The results of this study indicate that BEC students agree the use of webtoon applications is effective in improving aspects of reading comprehension, especially in determining the main idea, identifying references, making conclusions, and interpreting vocabulary. From the aspect of reading comprehension, students will be classified according to the level of reading comprehension, namely literal comprehension, inferential comprehension, critical comprehension and creative comprehension. based on the results of student interviews on the perception of the use of webtoons are classified based cognitive components, affective components and conative component. In addition, the results of exploring the benefits derived from the use of webtoons in the material are enhanced involvement, motivational factors, development of critical thinking skills and contextual education